Fusiones y adquisiciones : mecanismos de internacionalización de bancos latinoamericanos. (2017)
Since the 1990s, globally, there have been a large number of mergers and acquisitions (hereafter M & As) in the financial world whose objective is to leverage the international growth of the sector. As Latin American banks have not been the exception, we have examined whether M & As are internationalization mechanisms used by Latin American banks; For this, we chose as the case studies the main bank in Brazil, Colombia and Peru, observing the behavior of the indicator and dimensioning the degree of internationalization, during the period 1990-2014. We apply several measurement methodologies in order not to leave out important aspects of internationalization. The results of the study present evidence of the use of M & As by Latin American banks as internationalization strategies to reach new markets.